Determining key ecological indicators for urban land consolidation - Lin, Kuo-Liang (International Journal of Strategic Property Management, 2010)
Urban land consolidation, which reforms land parcels to remove fragmentation and produce ideal blocks, is an effective means of urban renewal. Successful urban land consolidation benefits city officials as well as the general public, in improved city image, increased land value, and more effective land use. However, urban land consolidation can be ecologically detrimental to the environment, while land consolidation has focused solely on development for human benefit. To remove the negative effects of urban land consolidation on the ecological system, this paper establishes a set of criteria for evaluating ecological impacts of an urban land consolidation plan. The current study first identifies key ecological indicators using a special group decision‐making process called “habitual domain analysis” and then records individual weighting of each indicator by an analytical hierarchy process, thus developing an urban ecological evaluation model with four levels and twenty‐three indicators. First Published Online: 18 Oct 2010